Optimal Quantity of Nano-Silicon for Electrospun Silicon/Carbon Fibers as High Capacity Anodes - Wang, Renheng; Sun, Yiling; Xiong, Keyu; Zheng, Junchao; Qian, Zhengfang; He, Zhenjiang (Frontiers in Chemistry, 2020)
Silicon/carbon composite nanofibers (Si@CNFs) are prepared as electrode materials for lithium-ion batteries via a simple electrospinning method and then subjected to heat treatment. The morphology and structure of the materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The results show that the structure provides good electrical and afford sufficient space to accommodate volume expansion during charging/discharging. Furtherly, the testing electrochemical performances display that the optimized Si@CNFs hold the initial reversible capacity at current density of 400 mA g-1 is 1820 mAh g-1, and the capacity retention of 80.7 % after 100 cycles at current density of 800 mA g-1. It is interested that the optimized Si@CNFs hold a superior capacity of 1000 mA g-1 (400 mA g-1), which is attributed to that carbon substrate nanofiber can accommodates the volume expansion of Si. The SEI resistance generated from the Si@CNFs samples are smaller than that of the Si nanoparticles, which confirms that SEI film generated from the Si@CNFs much thinner that of the Si nanoparticles. In addition, the connected carbon substrate nanofiber can form a fiber network to enhance the electronic conductivity.